2010
DOI: 10.1111/j.1464-410x.2010.09288.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial management of low‐risk localized prostate cancer in the UK: analysis of the British Association of Urological Surgeons Cancer Registry

Abstract: Study Type – Therapy (outcomes research)
Level of Evidence 2c OBJECTIVE To assess the patterns of care for low‐risk localized prostate cancer. Management of this condition is highly controversial, with a range of treatment options, but there are no published UK data. METHODS Data from the British Association of Urological Surgeons (BAUS) Cancer Registry were linked to the UK Association of Cancer registries postcode directory. The demographic and clinical characteristics, and the initial management of men diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 18 publications
(24 reference statements)
3
30
0
2
Order By: Relevance
“…Overall, patients believed surgery to be the best and most effective form of treatment. This corresponds with current treatment rates, which show that the majority of patients with LPCa opt for surgery [36].…”
Section: Radical Prostatectomysupporting
confidence: 80%
“…Overall, patients believed surgery to be the best and most effective form of treatment. This corresponds with current treatment rates, which show that the majority of patients with LPCa opt for surgery [36].…”
Section: Radical Prostatectomysupporting
confidence: 80%
“…Studies looking at low-risk deferred treatment trends in European populations were unable to report results by race due to relatively homogenous study cohorts. 10,28 Furthermore, an earlier SEER study did not report results by race. 11 Therefore, our findings that Caucasian men are more susceptible to aggressive treatment for indolent disease are novel and should guide future efforts that seek to reduce unnecessary aggressive treatment rates.…”
Section: Discussionmentioning
confidence: 98%
“…26,27 For example, studies from European populations have suggested that men of higher education level or from more affluent areas were more likely to seek aggressive treatment for prostate cancer-a behavior that may be driven by trust in providerdelivered therapies and willingness to receive treatment despite potential risks and side effects. 10,28 Schulman et al 29 found that patient race independently influences physician treatment recommendations, with physicians more likely to recommend aggressive therapy for white patients compared with black patients when presented with hypothetical cases of chest pain. Thus, it is possible that physicians may be more likely to recommend aggressive therapy for more affluent, Caucasian, or married patients with low-risk prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, where PSA testing is less prevalent, 20% of patients with localized PCa met the criteria for low-risk disease according to the classification of D'Amico et al [20,34] . Hence, the rigor of inclusion criteria and the PSA testing rate distinctly affect the proportion of men eligible for AS.…”
Section: Clinical Outcome and Implicationsmentioning
confidence: 99%